The Role Of Staffing And Orientation Practices In Predicting Service-Oriented Organisational Citizenship Behaviour - Mohd. Nasurdin, Aizzat; Ahmad, Noor Hazlina; Cheng, Ling Tan (Asian Academy of Management (AAM), 2016)
This study examined the relationships between two specifc human resource management practices (stafng and orientation) and service-oriented organisational citizenship behaviour. Survey data were gathered from a sample of 290 frontline employees attached to 4- and 5-star hotels in Malaysia. The partial least squares technique was used to test the research hypotheses. Results showed that stafng (consisting of recruitment and selection) and orientation have positive eﬀects on the three dimensions of service-oriented organisational citizenship behaviours. These fndings demonstrate the need for hotels to revisit their prevailing stafng and orientation practices in an attempt to enhance their employees' display of service-oriented citizenship behaviours